2020
DOI: 10.1088/1361-6463/ab78d9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional resonant acoustic wave router

Abstract: We demonstrate that asymmetric 3-port devices can be used to design a multi-functional set-up operating as a symmetric combiner and splitter at the same frequency. For a concrete implementation of the proposed multi-functionality protocol, we employ a resonant acoustic 3-port device operating in a subwavelength regime, showing splitting/combining abilities with nearly perfect transmission in presence of losses, induced by the interactions of the system's resonances. Finally, as an extension of the 3-port multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Meanwhile, subwavelength resonant acoustic structures were used to perform wave routing functionalities that were controlled by an adapted input wavefront (40)(41)(42), following the above-mentioned idea of "controlling light with light" (11)(12)(13)(14)(15). These works differ from ours chiefly in that the input wavefront rather than the scattering system determines the wave routing functionality, relegating the functionality control to wave sources that must offer multichannel coherent control.…”
Section: Signal Routing In Nanophotonics and Acousticsmentioning
confidence: 99%
“…Meanwhile, subwavelength resonant acoustic structures were used to perform wave routing functionalities that were controlled by an adapted input wavefront (40)(41)(42), following the above-mentioned idea of "controlling light with light" (11)(12)(13)(14)(15). These works differ from ours chiefly in that the input wavefront rather than the scattering system determines the wave routing functionality, relegating the functionality control to wave sources that must offer multichannel coherent control.…”
Section: Signal Routing In Nanophotonics and Acousticsmentioning
confidence: 99%
“…22 Among them, the four-port diffraction gratings are widely used in many fields due to their good diffraction efficiency and flexibility. [23][24][25][26][27][28] Therefore, it is necessary to propose a four-port beam splitter with high diffraction efficiency. In recent years, some works have reported that performance can be improved through novel grating structures.…”
Section: Introductionmentioning
confidence: 99%
“…Ramezani et al proposed parity-time-symmetric impedance matched media without breaking reciprocity [20]. Richoux et al demonstrated the splitter and combined function by waveguides loaded with Helmholtz resonators [21,22]. Mouadili et al theoretically proposed an acoustic demultiplexer with slender tubes based on Fano induced transparency resonances [23].…”
Section: Introductionmentioning
confidence: 99%